A business strategic study of facilities development in south east sematera under gross split production sharing contract - Aversie, Herdon; Budi Saksono, Prasetyo (The Indonesian Journal of Business Administration, 2018)
Abstract. To many countries in the world, oil and gas sector has been vast areas that become a strategic sector to its nation in parts of country and region stabilization. It also becomes a vital commodity in countries that mainly could affect its economic country’s conditions. South East Sumatera (SES) block has been a part of Indonesia’s oil and gas production area whereas its contribution from 1960’s until present time. Under a Production Sharing Contract (PSC) agreement, SES block is one of the largest offshore producers of crude oil in Indonesia. However with regards to implementation of new regulation on September 2018, the Production Sharing Contract is to be terminated and handed over to the new contract holders/operator. Therefore business strategic plans to develop South East Sumatera aging facilities are imperative. The research for facilities development in South East Sumatera (SES) initialize by provides a general comparison between ongoing production sharing contract agreement and new gross split production sharing contract. Furthermore, the methodology of this research are by a qualitative method to knows facilities development options and followed by a quantitative method by uses a Net Present Value (NPV) calculation and NPV Index (%) approaches, to calculates the profitability figures for each facilities development options. Based on the analysis, it shows detrimental comparison in the new gross split production sharing contract, in which efficiency factor on production costs as well effectiveness factor of work program are turn out to be the most outstanding concern in the new gross split production sharing contract. The conclusion from Net Present Value (NPV) calculation and NPV Index (%) shows that options which has less initial investment is potential as the most profitable values. Further as part of management implication and scenarios development, it concluded essential to re-considers as well to the factors of potential production loss, technology level requirement and potential of local environment effect. Hence from this study, it concludes and recommends an offshore facilities development after contract hand-over is to develop a distribution pipeline and to develop an offshore platform refurbishment; whereas these options have potential profitability values as well in consideration of potential production loss in case if said options are non-executed. Addition recommendation to support above is to perform a detail study and analysis of new-build platforms in integration between personnel accommodations and power generation facilities as part core support of oil production activities in South East Sumatera (SES). This study is expected to provide an outlook of potential facilities development options to the new contract holder/operator, at the same time as to provide an outlook of investment figures necessary in regards to develop offshore facilities in South East Sumatera (SES).Keywords: production sharing contract, gross split, profitability, offshore facilities development and production loss.